1993
DOI: 10.1111/j.1365-2958.1993.tb01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction and pathogenicity of Aspergillus fumigatus mutants that do not produce the ribotoxin restrictocin

Abstract: Aspergillus fumigatus, the most common cause of invasive pulmonary aspergillosis (IPA), produces a potent cytotoxin called restrictocin. To investigate the role of restrictocin in IPA, we have constructed fungal strains in which the res gene has been inactivated by gene disruption. These disruptants lack the specific extracellular ribonucleolytic activity associated with restrictocin, as measured by an in vitro rabbit reticulocyte lysate assay. Western blot analysis of one disruptant, using an anti-restrictoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 21 publications
(10 reference statements)
2
31
0
Order By: Relevance
“…Tang et al [6] and Smith et al [9] decreased the number of conidia to achieve 100% mortality (8 x 1 O5 conidia/mouse) by administration of the corticosteroid (1 12.5 mgkg) in five stages. In the present study, the inoculum required to produce infection was optimised to give reproducible survival curves and a 100% mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al [6] and Smith et al [9] decreased the number of conidia to achieve 100% mortality (8 x 1 O5 conidia/mouse) by administration of the corticosteroid (1 12.5 mgkg) in five stages. In the present study, the inoculum required to produce infection was optimised to give reproducible survival curves and a 100% mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most recent data have suggested that these enzymes are not major virulence factors . Recently, other metabolites, including cytotoxins have been studied [9][10][11]. The results of DNA typing methods have suggested a genomic polymorphism between A. fumigatus strains [ 12-1 61.…”
Section: Introductionmentioning
confidence: 99%
“…The deletion of the res gene to create mutants deficient in the ribonucleotoxin restrictocin did not have an effect on virulence or fungal burden in neutropenic models of IA (185). However, culture filtrates of restrictocin mutants were unable to suppress neutrophil-mediated hyphal damage, in contrast to filtrates from wild-type strains (84).…”
Section: Role Of the Neutrophilmentioning
confidence: 92%
“…Mitogillin is a small basic protein of approximately 18 kDa with cytotoxic activity released by A. fumigatus (16,17,31). Together with the related toxins A. fumigatus allergen I (AspfI), restrictocin from Aspergillus restrictus (20), and ␣-sarcin from Aspergillus giganteus (26), mitogillin is a member of a family of conserved RNases that cleave a single phosphodiester bond of the 29S rRNA of eukaryotic ribosomes (11,16,17).…”
mentioning
confidence: 99%